A comparison of pollinator fig wasp development in figs of Ficus montana and its hybrids with Ficus asperifolia. Issue 3 (September 2015) - Ghana, Salah; Suleman, Nazia; Compton, Stephen G.
Abstract Figs (Moraceae) and pollinator fig wasps (Hymenoptera: Agaonidae) have a highly specific mutualistic relationship but fig wasps occasionally enter atypical hosts, and this can lead to hybrid fig trees and the potential for gene flow between species. Many fig trees are dioecious, with fig wasp offspring developing in galled ovules inside figs on male trees, whereas seeds develop only in figs on female trees. We generated experimental hybrids between the Asian Ficus montana Blume and a closely related African species Ficus asperifolia Miquel. Male F1s were sterile if entered by Kradibia tentacularis (Grandi) (Agaonidae), the pollinator of F. montana, because its offspring always failed to develop, without ovule enlargement. As with the F1s, figs on most male backcross plants [F. montana × (F. montana × F. asperifolia)] also aborted shortly after pollinator entry, resulting in a higher turnover of figs than with F. montana, although the times taken for the figs to reach receptivity were similar. Pollinator larvae nonetheless consistently managed to develop inside the figs of one backcross plant and also occasionally in a few figs from another backcross individual. In these figs, galled ovules developed as normal, whereas in figs that aborted the galled ovules failed to enlarge. The sex ratio of K. tentacularis progeny in the backcross figs was female biased and did not differ from that in F. montana figs. Sycoscapter spec. (Hymenoptera: Pteromalidae), a parasitoid of K. tentacularis, was able to lay eggs and developed normally inside male backcross figs where its host was present.